Investigating Early-Stage Process Flow and Reactor Sequencing to Maximise Gold Extraction ln the Thiosulphate Leaching of Waste Printed Circuit Boards - Gonte, Melissa (Department of Chemical Engineering, 2024)
Fast growing volumes of waste electronic and electrical equipment (WEEE) present a rising environmental challenge while offering opportunities for creating a circular economy. Once dismantled and sorted, waste printed circuit boards (PCBs) are one of the value-bearing fractions of WEEE. Waste PCBs contain valuable metals like copper (Cu) and gold (Au) that can be profitably recovered using metallurgical methods like hydrometallurgy, pyrometallurgy, or a combination of the two. Successful implementation of pyrometallurgical technologies have been demonstrated in large-scale integrated recycling operations. These require high capital investment, large volumes of waste, and advanced scrubber/filter equipment to combat toxic flue gas pollution. Hydrometallurgical technologies present a viable processing route for the African context, where waste volumes are relatively low and energy supply is uncertain and expensive. Many lixiviants, such as cyanide, halides and aqua regia can be used to extract Au from waste PCBs. Due to its great selectivity and relatively low toxicity, this research focuses on the ammonium thiosulphate chemistry for the extraction of Au from waste PCBs. While ammonium thiosulphate solutions are effective in dissolving Au, there are challenges regarding reagent consumption when the system is used on materials that contain significant quantities of Cu. This is because Cu dissolves preferentially and plays a role in catalysing the breakdown of the thiosulphate ion. The method of pre-treatment and the sequence in which metals are leached in a multi-stage leach process determine the presence of co-existing metals, especially Cu for dissolution from waste PCBs in an ammonia thiosulphate system. In this work we hypothesized that the extraction of Au prior to delamination and size reduction will reduce the loss of Au, owing to Au being situated on the topmost layer of discarded PCBs. It would also result in less exposure of Cu to the leaching system which would ultimately limit reagent consuming side reactions. Four potential leaching sequences were examined to evaluate Au extraction, Au loss and base metal (BM) (Cu and Ni) co-extraction. Sequences A and B involved Au leaching of cut (A) and shredded (B) PCBs using a 0.5M ammonium thiosulphate ((NH4 )2S2O3) in the presence of 0.04M copper sulphate (CuSO4) and 1M ammonia (NH3), at a solid/liquid ratio of 100g/L. Sequences C and D involved BM extraction from cut (C) and shredded (D) PCBs prior to Au leaching, under the same conditions. iv The results showed that sequence A had the highest Au extraction of 97% Au. However, the coextraction of Cu and Ni, was also high at 21% Cu and 96% Ni, respectively. Nevertheless, in this study, this was preferable due to the considerable Au loss that other sequences experienced. Sequence D, B, and C, each suffered an overall Au loss of 53% , 26% and 20%, respectively. Leaching of Au leaf (93.1% Au) in the presence of predetermined amounts of Cu and Ni in 0.5M (NH4)2S2O3 and 0.5M sodium cyanide (NaCN) was used to simulate the leaching of Au from waste PCBs. Within the first hour of leaching, a high Au extraction of 99% and 88% was achieved in (NH4)2S2O3 and NaCN solutions, respectively, in the absence of background Cu and Ni. Addition of predetermined quantities of Cu (11500 mg) and Ni (519 mg) in both lixiviants resulted in a decline in Au extraction to 42% and 37%, respectively. The actual leaching of PCB in the same concentrations of (NH4)2S2O3 and NaCN gave 97% and 38% Au extraction, respectively. The optimisation tests (of sequence A) showed that a 0.5M(NH4)2S2O3 and 1M NH3 lixiviant concentration and a solid to liquid (S/L) ratio of 100g/L was optimal for leaching. Under these conditions 99% Au was extracted within 7.5 hours. In comparison, 36% Au extraction was achieved when NaCN was used for leaching under the same conditions. This showed that it is difficult to implement the optimal sequence, obtained for (NH4)2S2O3 leaching, in the leaching of waste PCBs using NaCN. NaCN suffers from the interference of foreign ions as side reactions compete for the reagent. Other than NaCN's level of toxicity, the results suggest that this system also requires implementation of the prior removal of BMs before leaching of Au. In conclusion, the highest Au extraction occurs when Au is extracted from PCBs using sequence A (before delamination, aggressive size reduction, and BMs extraction). Sequence A's low coextraction of Cu demonstrates that most of the Cu remains interlocked within the boards during Au extraction.